Human leptospirosis in the Marche region: Over 10 years of surveillance. (28th January 2021) - Magi, Gloria; Mingoia, Marina; Morroni, Gianluca; Fioriti, Simona; Coccitto, Sonia Nina; Di Sante, Laura; Giovanetti, Eleonora; Brenciani, Andrea
Abstract: We conducted a 10 years' retrospective study in 347 symptomatic individuals to assess the regional distribution of leptospirosis. A total of 173 individuals were diagnosed positive (49.8%): 11.5% were found positive to Leptospira by microscopic agglutination test positive, whereas 38.3% were found positive by microscopy analysis. The maximum peak of leptospirosis was reached in 2017 ( n  = 32). The most common serovars were Icterohaemorrhagiae and Poi.